2007
DOI: 10.1159/000099099
|View full text |Cite
|
Sign up to set email alerts
|

Serum Chitotriosidase Activity, a Marker of Activated Macrophages, Predicts New Cardiovascular Events Independently of C-Reactive Protein

Abstract: Background: C-reactive protein (CRP) is a well-established inflammation marker associated with cardiovascular risk. However, its relationship with chitotriosidase activity, a novel marker of activated macrophages highly expressed in human atherosclerotic plaques, is unknown. Therefore, we sought to determine if serum chitotriosidase activity predicts the risk of new coronary events, and to analyze its relationship with CRP. Methods: Chitotriosidase activity and genotype, and high-sensitivity CRP were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…28,29 In a related study, Artieda et al also showed that chitotriosidase activity predicts the risk of new adverse cardiovascular events in a follow-up period of 4 years. 30 Canudas et al reported that serum chitotriosidase activity is not associated with lipid levels before and after treatment with statins, which suggests that plasma lipid level alteration does not affect macrophage chitotriosidase expression level in vivo 31 and is in accordance with our study, showing no correlation between blood lipid levels and chitotriosidase activity.…”
Section: Discussionsupporting
confidence: 92%
“…28,29 In a related study, Artieda et al also showed that chitotriosidase activity predicts the risk of new adverse cardiovascular events in a follow-up period of 4 years. 30 Canudas et al reported that serum chitotriosidase activity is not associated with lipid levels before and after treatment with statins, which suggests that plasma lipid level alteration does not affect macrophage chitotriosidase expression level in vivo 31 and is in accordance with our study, showing no correlation between blood lipid levels and chitotriosidase activity.…”
Section: Discussionsupporting
confidence: 92%
“…[16][17] Chit activity seems to be related to the severity of atherosclerotic lesions, thereby suggesting a possible role for Chit as a marker of atherosclerotic extension. [18][19][20] In addition, it was reported that patients with atherothrombotic stroke (ATS) and ischemic disease (IHD) had significantly higher Chit activities than the control group. 19 However, ATS subjects had higher Chit activity than IHD subjects, whose atherosclerosis is localized more specifically in coronary vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Serum CHIT activity was more prominent in stroke patients than in patients with ischemic heart disease, suggesting more widespread atherosclerosis. In a related study, Artieda et al (2007) also showed that CHIT activity predicts the risk of new adverse cardiovascular events within a follow-up period of four years 21) . Canudas et al (2001) reported that serum CHIT activity is not associated with lipid levels before and after treatment with statins, which suggests that plasma lipid level alteration does not affect the macrophage CHIT expression level in vivo and is in accordance with our study, showing no correlation between blood lipid levels and CHIT activity 22) .…”
Section: Chitotriosidase and Biochemical Markersmentioning
confidence: 95%